Left upper lobectomy with bronchoplasty in uniportal video-assisted thoracic surgery for bronchial carcinoid - Zhang, Zhi (J Vis Surg, 2016)
A 36-year-old male smoker presented with a bronchial carcinoid in the left upper lobe (LUL) associated with bronchial occlusion of the LUL bronchus. A left upper lobectomy with bronchoplasty was performed through a 3.5 cm single-incision in video-assisted thoracic surgery (VATS). The procedure was successful and the recovery uneventful. Pathological examination revealed a carcinoid tumor with no lymph node involvement (T1bN0M0). The follow-up bronchoscopy and computed tomography (CT) scan confirmed no stenosis and no signs of recurrence.